IN FAULT DETECTION AND RELIABILITY ENHANCEMENT ALGORITHM FAILURE CALCULATION METHODS - Usmonov , Shukurillo Yulbarsovich (Educational Research in Universal Sciences, 2023)
It uses a multivariate experimental modeling algorithm to obtain a mathematical description of the electrical behavior of the system and the method in the presence of a fault current (Fig. 3.4). The algorithm compares the modeled result with the measured result and quantifies the resulting parameter comparison by obtaining the relevant signals. The identified input signals are fed to the artificial neural network and the process speed is fed to the convolutional system.